2017
DOI: 10.1136/archdischild-2017-313071
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated paediatric Outpatient Parenteral Antimicrobial Therapy medical support: a pre–post observational study

Abstract: The introduction of a formal medical team to HiTH demonstrated a positive clinical impact on OPAT patients' outcomes. These findings support the ongoing utility of medical governance in a nurse-led HiTH service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 20 publications
2
12
1
Order By: Relevance
“…Whilst there is a developing body of evidence addressing the clinical outcomes of children requiring OPAT [4,10], it is also clear that there is a real deficit of evidence about the experiences of children and their parents [15] and almost no literature considering the perspectives of clinicians. This study addresses this deficit by exploring these perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst there is a developing body of evidence addressing the clinical outcomes of children requiring OPAT [4,10], it is also clear that there is a real deficit of evidence about the experiences of children and their parents [15] and almost no literature considering the perspectives of clinicians. This study addresses this deficit by exploring these perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…It also a reflects other policies such as reducing the length and number of inpatient stays, a belief that OPAT is a more cost-effective option when compared to continued inpatient care [7][8][9] and it may reduce healthcare-associated infections [1]. However, OPAT is not without risk [10] and a systematic review concludes further improvements in paediatric OPAT are needed for safe and effective implementation [4]. Additionally, few studies have reported in any detail about the OPAT experiences of children and their parents.…”
Section: Introductionmentioning
confidence: 99%
“…This crucial involvement can improve clinical outcomes, decrease antimicrobial resistance, and reduce the cost of treatment. Other studies demonstrated that the involvement of an infectious diseases physician in these programs has reduced re-admissions and emergency room visits [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…The growing evidence about the clinical outcomes of OPAT for children2 5 10 has overlooked the perspectives and experiences of children and their parents12 and a mix of methodological issues and the age of the studies limits the utility of this evidence to current practice. The suggested standardised survey for routinely collecting patient/parent satisfaction1 is unlikely to generate the range and depth of experience that will illuminate practice.…”
Section: Discussionmentioning
confidence: 99%
“…Outpatient parenteral antimicrobial therapy (OPAT) for children is the parenteral administration of antimicrobials for at least two consecutive days without an intervening hospitalisation 1. Children with suspected serious bacterial infections2–6 but who are sufficiently stable and where other factors (eg, child’s medical history) are taken into consideration may be appropriate for OPAT. Children are most commonly referred to OPAT after a period of hospitalisation, but in some cases directly from the emergency department.…”
Section: Introductionmentioning
confidence: 99%